Pengaruh Pelatihan terhadap Kinerja Asisten Pembiayaan di PT Bank BNI Syariah - Rizqi Adhyka Kusumawati (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This study aims to evaluate the training process in the Learning Centre Unit at PT Bank BNI Syariah, (Persero), Tbk. This research is qualitative data collection methods in the form of observation and interviews with parties which is directly related to the activities of the Learning Centre Unit and the training participants. The list of questions had been structured according to Kirkpatrick & Kirkpatrick's theory as well as theory prevailing performance. Respondents are employees of PT Bank BNI Syariah (Persero), Tbk. especially those who served as a Financing Assistant. The results of observations and interviews show that there is an influence between training and improving the performance of PT Bank BNI Financing Assistant Syariah, (Persero) Tbk. and the behaviour level is the most variable dominantly affect the increase in employee performance after getting training. This is indicated by the percentage increase in the pre-test value and post-test and achievement of employee targets after attending training. Result interviewed 30 participants from 3 generations who attended the training said that 75% of the training participants were very helpful and happy get training so that helps them in completing work with new knowledge and ways.